(untitled) (Research, Society and Development, 2021)
Background: the use of medicinal plants with mosquito repellent properties constitutes an effective alternative, ecologically appropriate, and less aggressive to the environment. Objective: to present a protocol for a systematic review of clinical trials involving medicinal plants with mosquito repellent activity. Methods: the literature search was carried out using the Science Direct, SciELO, SciFinder, Springer, PubMed/MEDLINE, Scopus, and Web of Science databases. The search was carried out in August 2021 and included some work published in the Portuguese, English, or Spanish languages. The titles, abstracts, and articles in full were analyzed by three reviewers, independently, to identify the relevant studies. The referred protocol was registered in the International Prospective Register of Systematic Reviews (PROSPERO) and the systematic review will be conducted according to the guidelines for Preferred Reporting Items for Systematic Reviews and Meta-Analyzes (PRISMA). Final considerations: the search for new repellents derived from plants that are standardized, effective, and safe in the prevention of diseases transmitted by mosquitoes makes it relevant to carry out a systematic review.